PRESERVING THE NATURAL LANDSCAPE ON THE CONSTRUCTION SITE FOR SUSTAINABLE ECOSYSTEM - Sokolov, Nikolay; Ezhov, Sergey; Ezhova, Svetlana (Journal of Applied Engineering Science, 2017)
Development and extension of urban infrastructure increasingly frequently involves the areas with compound relief forms. From the environmental point of view it is vitally important to preserve the unique landscapes for future generations. Innovative approaches meant to stabilize and reinforce ground on the building construction sites, particularly on slopes, solve the defined engineering problem. The paper addresses a case study of geotechnical design and construction practice in the complex conditions.